2019
DOI: 10.1038/s41419-019-1663-5
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of TC2N as a novel promising suppressor of PI3K-AKT signaling in breast cancer

Abstract: Although TC2N has proven to be an oncogene in lung cancer, its biological function and molecular mechanisms in other cancer still remains unclear. Here, we investigate in breast cancer that TC2N expression is sharply overexpressed in breast cancer specimens compared with normal breast specimens, and the low TC2N expression was associated with advanced stage, lymphatic metastasis, larger tumors and shorter survival time. Upregulation of TC2N significantly restrains breast cancer cell proliferation in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 29 publications
4
27
1
Order By: Relevance
“…The overexpression of TC2N in AGS cells significantly increased the cell proliferation, and promoted cell migration and invasion, whereas the knockdown of TC2N exerted the opposite effects, which is consistent with previous studies, which reported an oncogenic function of TC2N ( 10 , 11 ). Cell proliferation is predominantly regulated by the cell cycle, which is a complex network of regulatory process involving multiple signaling pathways ( 19 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overexpression of TC2N in AGS cells significantly increased the cell proliferation, and promoted cell migration and invasion, whereas the knockdown of TC2N exerted the opposite effects, which is consistent with previous studies, which reported an oncogenic function of TC2N ( 10 , 11 ). Cell proliferation is predominantly regulated by the cell cycle, which is a complex network of regulatory process involving multiple signaling pathways ( 19 ).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, determining the molecular mechanism underlying the development of gastric cancer is required. TC2N was recently identified as a novel oncogene in lung cancer ( 10 , 11 ); however, the role of TC2N in gastric cancer remains unclear. In the present study, upregulated expression levels of TC2N were identified in gastric cancer cells and tumors of patients with gastric cancer via TCGA analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the essential roles of protein containing the C2 domain in endocytosis, cellular metabolism and cancer [29][30][31]. TC2N expression is also associated with the prognosis and development of human lung cancer and breast cancer [16][17][18]. Former researchers have found that TC2N overexpression in lung cancer leads to enhancing the proliferation ability and inhibiting apoptosis through the repression of p53 function in a transcription-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the essential roles of protein containing the C2 domain in endocytosis, cellular metabolism and cancer [29][30][31]. TC2N expression is also associated with the prognosis and development of human lung cancer and breast cancer [16][17][18]. Former researchers have found that TC2N overexpression in lung cancer leads to enhancing the proliferation ability and inhibiting apoptosis through the repression of p53 function in a transcription-dependent manner.…”
Section: Discussionmentioning
confidence: 99%